ANALISIS KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PEGAWAI DINAS SOSIAL KABUPATEN PASURUAN - Anggraeny, Nenny; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of competence and work environment on employee performance, as well as the mediating role of organizational commitment at the Social Service Office of Pasuruan Regency. Specifically, this research examines the direct effect of competence and work environment on employee performance, their impact on organizational commitment, and the effect of organizational commitment on employee performance. In addition, the study evaluates the mediating role of organizational commitment in the relationship between competence and work environment on employee performance. A quantitative approach was employed using a census technique, involving 60 employees as respondents. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS 3.0 software. The results show that both competence and work environment have a positive and significant effect on employee performance and organizational commitment. Organizational commitment also has a significant impact on employee performance. Furthermore, organizational commitment acts as a mediating variable that strengthens the influence of competence and work environment on employee performance.